Correlation between Church Digital Ministry and Semarang Baptist Youth's Spirituality - Yesaya Bangun Ekoliesanto; Samuel Agus Santoso; Ayin Claudia (Sekolah Tinggi Teologi Simpson Ungaran, 2022)
The spirituality of today's young generation is very prone to be bad. The church needs to serve the younger generation in a way acceptable to them. This study aims to see the correlation between church digital ministry and the spirituality of Baptist youths throughout the city of Semarang. This research used quantitative approach with survey research methods. It shows that the Baptist churches' digital ministries were in the medium category and the Baptist youth's spirituality was in the moderate category, while digital ministry of the churches correlated strongly and positively to their youth's spirituality.